Thermoanemometric method for the measurements of flow velocity and temperature - Kurkowski, M.; Biernacki, Z.; Zloto, T. (Видавництво Національного університету "Львівська політехніка", 2001)
The paper deals with some problems concerning the measurements of flow intensity. In such measurements appropriate variants of thermistor sensors are used. The methodology of measurements, the analysis and the visual representation of signals by means of measuring card PCL818 and package DasyLab are presented.